Entre acolhimento e "adaptação": brincar e cuidar na chegada das crianças na educação infantil - Silva, Letícia Ferreira da (Universidade Federal de São Carlos, 2025)
This final course paper aims to research, through available literature, the difficulties and strategies used by education professionals during the school adaptation period in early childhood education institutions, and to investigate how play and sheltering can assist in this process. To this end, a qualitative bibliographic research was carried out through searches in databases of theses and dissertations on the subject, where three dissertations were selected for analysis, all with field research that allowed verification through direct observation of the practices carried out by education professionals in school institutions. It was observed that the difficulties reported often highlight the lack of direct planning that takes into account the specificities of this period, as well as the strategies, although helpful, lacking directions based on the needs of children and families. Thus, a weakness is noted regarding theoretical and legislative support, requiring greater guidance to orient teachers to navigate this period.
Between welcoming and "adaptation": playing and caring upon children's arrival in early childhood education
Keywords: Adaptação; Acolhimento; Educação Infantil; Brincar; Cuidado; Adaptation; Sheltering; Early Childhood Education; Play; Carefull; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade